(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
This paper presents a systematic analysis of the changes in thickness and the differences in the heat flux transfer for the two surfaces of selected single-side napped fabric, to explore the relationship between their heat flux and thickness during compression. The results showed that heat flow in the un-napped surface was greater than that in the napped surface when the fabric initially contacted the upper plate of a Fabric Touch Tester (p ‹ 0.05); few differences of the heat flux between the un-napped and the napped surfaces measured separately with each surface facing upwards for each fabric type were observed when the pressure exceeded 0.6 Pa (p › 0.05); the heat flux was linearly correlated with thickness for both the un-napped surface and napped surface when the pressure exceeded 0.6 Pa (correlation coefficient R² › 0.9); the gradients of the regression equation of heat flux-thickness gradually increased from the initial thickness point to the midpoint of the maximum pressure except for the first heat peak point of the un-napped surface. In conclusion, heat flux was significantly affected by the surface characteristics of the fabrics in the initial stages of compression but was then not affected by either the surface features or the fabric structures at higher levels of compression pressure. The conclusion could be useful in product development and in providing a guide for clothing wearing comfort.